2012
DOI: 10.1039/c2cp23988d
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gas-phase ozonolysis rate coefficients of a number of sesquiterpenes at elevated temperatures using the relative rate method

Abstract: The rates of ozonolysis of four sesquiterpenes, β-caryophyllene, α-humulene, isolongifolene and α-cedrene, are determined in the gas phase at an elevated temperature of 366 ± 3 K and a pressure of ~780 Torr using the EXTreme RAnge chamber (EXTRA). The experimentally obtained rate coefficients agree with extrapolated room temperature rate coefficients for isolongifolene and α-cedrene but not for β-caryophyllene and α-humulene, which were found to be three orders of magnitude slower than this in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…We had found that the ozonolysis of β-C on AN:W surfaces proceeds ∼20 times faster than in the bulk liquid saturated with ozone, 30 and orders of magnitude faster than in the gas-phase. 10,44 We confirmed that 1-octanol is inert toward O 3 (g) under present conditions ( Fig. S1), in accordance with the negligibly small rate constant: k O3+1-octanol ≤ 0.8 M -1 s -1 in bulk water.…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentsupporting
confidence: 85%
“…We had found that the ozonolysis of β-C on AN:W surfaces proceeds ∼20 times faster than in the bulk liquid saturated with ozone, 30 and orders of magnitude faster than in the gas-phase. 10,44 We confirmed that 1-octanol is inert toward O 3 (g) under present conditions ( Fig. S1), in accordance with the negligibly small rate constant: k O3+1-octanol ≤ 0.8 M -1 s -1 in bulk water.…”
Section: Page 3 Of 23 Acs Paragon Plus Environmentsupporting
confidence: 85%
“…Ozonolysis is a significant pathway for ambient β-C removal; the relative contribution of O 3 reaction to tropospheric degradation is as much as 98 % (Hoffmann et al, 1997). Even though the reported reaction rate of β-C dark ozonolysis varies (Ghalaieny et al, 2012;Shu and Atkinson, 1995), aerosol is readily formed in this chamber and in other previous studies (e.g., but not limited to; Ng et al, 2006;Winterhalter et al, 2009;Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 57%
“…Up to now, only three literature studies exist that investigated the rate coefficient of the reaction of ozone with these SQTs. [20][21][22] Reported rate coefficients differ by more than two orders of magnitude for the two atmospherically most important SQTs, b-caryophyllene and a-humulene, apparently strongly motivating a reinvestigation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ghalaieny et al 21 carried out relative rate experiments in the EXTRA chamber (volume: 123 liter, Teflon-coated) at 366 AE 3 K and 780 Torr of a N 2 -O 2 mixture. GC-FID analysis served for the detection of the SQT and the reference substance applying a gas loop for sampling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation